Disparities in human papillomavirus (HPV) vaccine initiation and completion based on sexual orientation among women in the United States. Issue 2 (1st February 2021) - Adjei Boakye, Eric; Osazuwa-Peters, Nosayaba; López, Julia; Pham, Vy T.; Tobo, Betelihem B.; Wan, Leping; Schootman, Mario; McElroy, Jane A.
ABSTRACT: Objectives: We compared HPV vaccine initiation and completion of heterosexual with lesbian and bisexual (LB) women. Methods: We aggregated National Health and Nutrition Examination Survey data from 2009 to 2016 for 3, 017 women aged 18 to 34 y in the United States. HPV vaccine initiation was defined as reported receipt of ≥1 dose of the vaccine and completion as receipt of the three recommended doses. Weighted percentages and multivariable logistic regression models were used to examine differences in HPV vaccine initiation and completion between heterosexual and LB women. Results: Approximately 12% of respondents self-identified as LB women. Overall, a higher percentage of respondents (26%) had initiated the HPV vaccine than completed the three vaccine doses (17%). In the bivariate analysis, LB women had higher initiation ([35% of LB women versus 25% heterosexual]; p = .0012) and completion rates ([24% of LB women versus 17% heterosexual]; p = .0052) than heterosexual women. After adjusting for covariates, compared to heterosexual women, LB women were 60% (aOR = 1.60, 95% CI: 1.16–2.19) more likely to initiate and 63% (aOR = 1.63, 95% CI: 1.12–2.37) more likely to complete the HPV vaccine. Conclusions: Although LB women had higher likelihood of HPV vaccine initiation and completion compared with heterosexual women, their HPV vaccine uptake was well below the Healthy People 2020 target (80%). Understanding differences in the drivers of vaccine uptake in the LB population may inform strategies that would further increase HPV vaccine uptake toward achieving the 80% completion target.